Beyond One-Size-Fits-All: Integrating Traditional Knowledge and Addressing Historical Trauma and Health Inequities in New Zealand for South-Asian Communities - Lee, Bible; Kaur-Devgun, Navneet (Asian Academics in Aotearoa Association (A4), 2025)
New Zealand is now home to approximately 350,000 South Asians, and many carry unacknowledged, intergenerational historical trauma that profoundly shapes their health experiences. The enduring legacies of the 1947 Partition, British colonisation, including famines caused by colonial policies that resulted in millions of Indian deaths to enrich the British colonial empire, have left deep psychological and other intergenerational health imprints. Currently, many South Asians in Aotearoa still actively draw upon traditional healing systems alongside Western medical treatment. Yet, these ancient and community-validated practices remain largely invisible and unacknowledged in mainstream clinical settings. Traditional South Asian health knowledge, such as Ayurveda, Unani medicine, Siddha, and spiritual healing, is often disregarded or dismissed within Aotearoa New Zealand’s clinical contexts as lacking empirical evidence. This research addresses this critical gap by exploring how traditional and historical South Asian healing knowledge can be meaningfully recognised, respected, and woven into Aotearoa’s healthcare landscape to provide more holistic care for South Asians in Aotearoa. This mixed-methods study involves semi-structured interviews with 20 South Asian adults living outside Auckland, a systematic literature review, and a demographic survey. Guided by Kaupapa Māori methodology, the project honours traditional South Asian health knowledge as taonga and upholds cultural safety and epistemic justice as central principles. This study contributes to the growing field of Asian health equity research in Aotearoa by establishing an evidence base for policymakers, clinicians, and researchers. The project highlights the importance of respecting, integrating, restoring and valuing traditional and historical South Asian health knowledge within culturally responsive and equitable healthcare systems for New Zealand’s fastest-growing population. Importantly, this project argues that Aotearoa’s public health system does not need to remain solely biomedical and Western-dominated. Instead, it should evolve to embrace pluralistic approaches and find opportunities to honour both clinical efficacy and culturally grounded methods that reflect the diversity of its people.